2018
DOI: 10.21037/tlcr.2018.05.05
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification in lung cancer screening

Abstract: Lung cancer screening has been shown in the National Lung Screening Trial (NLST) to result in a statistically significant decrease in lung cancer specific mortality. Also within that trial there was shown to be a 7% decrease in all-cause mortality. While the reasons for this benefit are not entirely clear, it may relate to the detection and treatment of other important findings. Smokers not only have a higher risk of lung cancer, but also increased risk of atherosclerosis. The latter can be detected by the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
2
24
0
5
Order By: Relevance
“…20,21 Furthermore CACS obtained from nongated CT scans for lung cancer screening has been demonstrated as a valuable biomarker in diagnosis and risk prediction for coronary heart disease. 31 In conclusion, we investigated the impact of coronary artery calcification on intradialytic BP patterns in patients with ESRD on maintenance hemodialysis. CACS measured using nongated chest CT scans was associated with widened pulse pressure, but was not related to either intradialytic hypotension or hypertension.…”
Section: Figmentioning
confidence: 99%
“…20,21 Furthermore CACS obtained from nongated CT scans for lung cancer screening has been demonstrated as a valuable biomarker in diagnosis and risk prediction for coronary heart disease. 31 In conclusion, we investigated the impact of coronary artery calcification on intradialytic BP patterns in patients with ESRD on maintenance hemodialysis. CACS measured using nongated chest CT scans was associated with widened pulse pressure, but was not related to either intradialytic hypotension or hypertension.…”
Section: Figmentioning
confidence: 99%
“…NLST data have shown that the presence of coronary artery calcification is associated with a 3 fold increase in cardiovascular death 12 . These studies suggest a concordance of CAD and lung cancer [11][12][13] . Therefore, adding patients who are receiving CTCS to a lung cancer screening cohort is reasonable on several levels.…”
Section: Discussionmentioning
confidence: 54%
“…The ASCVD risk is calculated based on age, sex, race, smoking status, blood pressure, cholesterol levels, smoking status and diabetic status 2 . Atherosclerotic cardiovascular disease shared risk factors with lung cancer which could explain the benefit of performing FCT on this population [11][12][13] . We concede that as tobacco rates decrease, the malignancy rate in IPN will also decrease, thereby erasing the benefit of FCT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This study suggests that there is benefit to lung cancer screening in other populations as well. Coronary artery calcification is frequently identified in patients undergoing lung cancer screening with LDCT [12][13][14] . NLST data have shown that the presence of coronary artery calcification is associated with a 3 fold increase in cardiovascular death 13 .…”
Section: Discussionmentioning
confidence: 99%